Relationship between Dissemination and Awareness of the University VMGO - Makie, Gleemoore; Buado, Ryan (Journal of Interdisciplinary Perspectives, 2025)
The effective communication of an organization's Vision, Mission, Goals, and Objectives (VMGO) is crucial for the institution’s success and stakeholders’ alignment. This study investigates the relationship between disseminating the University's Vision, Mission, Goals, and Objectives (VMGO) and its students' awareness level. The research design used a descriptive survey method to collect student data using a structured questionnaire converted into Google Forms. The questionnaire assessed the effectiveness of dissemination and the level of awareness of VMGO. The study investigated factors that may influence dissemination and the students' awareness, such as frequency, channels, and clarity of communication. The results showed a significant relationship between dissemination and awareness of VMGO. The study highlights the importance of robust communication strategies in fostering engagement and alignment with the organizational objectives. The findings can inform UCU's administration in refining its dissemination practices to enhance awareness and understanding of the institution's VMGO.